Enhancing awareness and preventing musculoskeletal disorders through stretching exercises in the Kintamani highlands - Indrayani, Ni Luh Dwi; Kamaryati, Ni Putu; Sriasih, Ni Kadek; Wulandari, Sarah Kartika; Suantika, Putu Inge Ruth (Universitas Muhammadiyah Magelang, 2025)
Musculoskeletal discomfort is a common problem among adults, especially those living in mountainous areas. If left untreated, this condition can lead to long-term musculoskeletal diseases. This community service program aims to increase public awareness and understanding of the importance of preventing musculoskeletal disorders through the implementation of proper physical stretching exercises. The methods used in this program include community education on the physical activities needed to prevent muscle and joint problems, consultations, and stretching practices supported by community assistance. By involving health workers and community leaders, this program provides counseling and training on six types of static stretching. As a result, there was a significant increase in the community's understanding and ability to demonstrate effective stretching techniques. The community also showed active involvement in raising awareness about the importance of musculoskeletal health and successfully implementing strategies for the prevention of muscle and joint diseases. Through a holistic approach involving community leaders and local health workers, understanding of musculoskeletal disorders increased, leading to a positive impact on the quality of life for the community, especially in highland areas.